Comparative Study Scent Quality or Smells, Cleanliness and Beauty to RPTRA User Satisfaction in Denpasar City - Paramitha, I Gusti Ayu Intan; Dwijendra, Ngakan Ketut Acwin (ASTONJADRO, 2023)
Open space is created to socialize with other humans. One of the existing open spaces, there is a Child-Friendly Integrated Public Space (RPTRA) as one of the programs to create a child-friendly city. The existence of this RPTRA helps the people in Denpasar City in carrying out activities in open spaces such as sports, children's play, education and as a green space because in the RPTRA there is greenery. This RPTRA is located in the center of Denpasar City so it is easy to reach by the community. This research was conducted to compare whether or not there is a difference between the two RPTRAs based on the comfort of the smell or smell, cleanliness and beauty from the user's point of view of each RPTRA, because one of these RPTRAs, namely the Lumintang Traffic Park RPTRA, has a TPS (Temporary Garbage Disposal Site) which is located approximately 100 meters from the RPTRA. With the research method used, namely the quantitative research method by distributing questionnaires to the people who are active in each RPTRA, it is found that the RPTRA Traffic Park has a lower percentage level of comfort compared to RPTRA Janggan Park. This is due to the fact that the temporary garbage dumps are located not far from the Taman Traffic RPTRA with the condition that waste often accumulates, which is the main factor for the discomfort of the people who are active in this RPTRA.